Religiosity and the Naturalness Bias in Drug and Vaccine Choices - Meier, Brian P. (Journal of religion and health, 2023)
Research reveals a bias for natural versus synthetic drugs. We sought to determine if this bias is associated with religiosity. Three cross-sectional studies (N = 1399 U.S. participants) were conducted to examine the impact of religiosity on the naturalness bias in the drug and vaccine domains. We assessed measures of religiosity, preferences for natural versus synthetic drugs and vaccines in hypothetical scenarios, and a health-related behavior (COVID-19 vaccination status). The results revealed that participants high versus low in religiosity had stronger preferences for natural versus synthetic drugs and vaccines. Furthermore, participants high versus low in religiosity were less likely to have taken the COVID-19 vaccine, and the natural drug bias was a mediator of this effect. Overall, participants higher in religiosity had a stronger preference for natural versus synthetic drugs and vaccines, and this preference had implications for health behavior.